3c-4d 3c+4d
( - )
4c-3d 4c+3d
12c^2 +9cd -16 cd -12d^2
(4c-3d ) ( 4c+3d) (по формуле (a+b) (a-b) =a^2 - b^2) 12c^2 -7 cd -12d^2 14 (4c-3d ) ( 4c+3d) : 4c+ 3d 12c^2 -7 cd -12d^2 (умножить на) 4c+3d (4c-3d ) ( 4c+3d) 14 (сокращаем) 12c^2 -7 cd -12d^2 4c^2-2cd 14 (4c-3d ) + 4c-3d (общий знаменатель 14 (4c-3d ). 4c-3d - домножим на 14) 12c^2 -7 cd -12d^2 +56с^2 -28cd =0 68c^2 -35cd -12d^2 =0 (под вечер мозг взорвался и был таков)
ответ:cos(-480°) = cos(360° - 480°) = cos(-120°) = cos(240°) = cos(180° + 60°) = -cos(60°) = -1/2
sin(-7π/4) = sin(-π/4) = -sin(π/4) = -1/√2
Подставляем значения: cos(-480°) - √2sin(-7п/4) = -1/2 - √2(-1/√2) = -1/2 + 1 = 1/2
Объяснение: просто изи с тебя